FIRM SIZE MODERATES THE EFFECT OF BANKRUPTCY POTENTIAL, AUDIT QUALITY, PUBLIC OWNERSHIP STRUCTURE ON AUDIT DELAY - Mulyani Mulyani; Kevin Kurniawan Santoso (Sean Institute, 2023)
Audit delay is one of the important factors related to the relevance of the information contained in the financial statements. The purpose of this study was to determine the effect of the potential for bankruptcy, the complexity of the company's operations, the structure of public ownership and the size of the company as moderating variables on audit delay. The statistical method used in this study is multiple linear regression and Moderated Regression Analysis with a significance of 5%. The sampling technique was determined based on the purposive sampling method so as to produce a total sample of 44 companies and obtained a total of 132 observations. T The conclusion of this study is that bankruptcy probability has a negative effect on audit delay, audit quality has a positive effect on audit delay, company size is able to moderate the relationship between bankruptcy potential and audit delay. On the other hand, there is insufficient evidence that public ownership structure and firm size affect audit delay, and there is insufficient evidence that firm size is able to moderate the relationship between audit quality and the relationship between public ownership structure and audit delay.